2021
DOI: 10.3390/healthcare9101350
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Addiction and Depression among Low-Income Boys since COVID-19: The Moderating Effect of Being an Only Child

Abstract: Even though boys’ depression has become important, and their smartphone use has increased since COVID-19, little is known about low-income middle and high school boys’ depression in the context of whether they have siblings. Thus, this study investigates the relationship between smartphone addiction and depression as well as the moderating effect of being an only child on the relationship. Participants were limited to middle and high school students whose families were regarded as having a low-income. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
(68 reference statements)
0
14
1
Order By: Relevance
“…In other words, the majority of the studies were conducted in countries belonging to the Asian continent. The number of participants in the studies ranged from 129 (Lee et al 2021) to 3615 (Duan et al 2021), with a male/female ratio of 0.78. The lowest average age in the studies was 11.29 ± 0.82 (Chen et al 2020), while the highest average age was 17.57 ± 1.89 (Lee et al 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the majority of the studies were conducted in countries belonging to the Asian continent. The number of participants in the studies ranged from 129 (Lee et al 2021) to 3615 (Duan et al 2021), with a male/female ratio of 0.78. The lowest average age in the studies was 11.29 ± 0.82 (Chen et al 2020), while the highest average age was 17.57 ± 1.89 (Lee et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…From this point of view, it can be concluded that there are different mediating/confounding variables that affect the relationship between internet/smartphone addiction and gender. For example, this mediator variable might be attention deficit and hyperactivity disorder (Kahraman and Demirci 2018) or there might be a problem such as the presence of depressive symptoms (Lee et al 2021). There is a need for meta-analysis studies examining the mediating variables in order to reach a definite opinion on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Given that elementary schoolchildren are not mature enough to effectively moderate behavior on their own, they might be less able to control their smartphone usage. 35 Additionally, due to the COVID-19-related online education requirements, their smartphone use may have increased. Many students may become overly reliant on smartphones, even if their parents supervised their usage.…”
Section: Discussionmentioning
confidence: 99%
“…And the detrimental economic effect of COVID-19 has made it more challenging to earn a living. 35 These all contribute to possibly an increase in the time they have to put in for work to maintain a similar level of income generated before the pandemic. That is, in low-income households, parents may not have enough time to manage their children’s smartphone use.…”
Section: Discussionmentioning
confidence: 99%
“…And income has a direct impact on interpersonal relationship. Research by Lee et al (2021) shows that low-income boys are at higher risk for smartphone addiction, and that smartphone use reduces the frequency and quality of their interactions with friends. Han (2013) finding that the interpersonal interactions of students at all levels are significantly affected by their family’s economic status.…”
Section: Introductionmentioning
confidence: 99%